AB0123 CHANGES IN CELLULAR GLYCOSYLATION AS A KEY FACTOR IN THE IMMUNOPATHOGENESIS OF SYSTEMIC LUPUS ERYTHEMATOSUS. (2nd June 2020) - Alves, I.; Pinto, V.; Santos-Pereira, B.; Campar, A.; Vizcaino, J. R.; Carneiro, F.; Vasconcelos, C.; Marinho, A.; Pinho, S.
Abstract : Background: Systemic Lupus Erythematous (SLE) is one of the most challenging autoimmune diseases as it may be presented as a severe, relapsing and disabling immune-mediated disorder still remaining incurable (1, 2). Protein glycosylation is an essential post translational modification that participate in the correct recognition of cells by the immune system (3–5). Moreover, glycosylation changes in T cells (specifically loss of branched N -glycans mediated by GnTV, encoded by MGAT5 gene) have been shown to impact its intrinsic function and activity in a diverse panel of autoimmune diseases (3, 4, 6) Objectives: To evaluate the impact of glycans in the cellular and molecular mechanisms underlying the loss of immune-tolerance, envisioning the identification of a new targeted-specific mechanism. Methods: We have analysed the profile of cellular glycosylation of a subset of biopsy-proven lupus nephritis from SLE patients and normal kidney tissue (from two Porto Centre Hospitals), through immunohistochemistry (IHC) as well as by real time PCR using RNA extracted from paraffin tissues. Blood samples were collected and were analysed by flow cytometry. Mgat5 null mice with 15-months old were monitored for autoimmune signs by evaluating proteinuria, weight loss and colon and kidney tissues were analysed by IHC and FACS. Results: SLE patients revealed a significant decreased expression of complex N -glycans in the renal parenchyma, when compared to healthy kidney. In addition, we have identified in lupus nephritis patients a unique subset of circulatory CD3 + T cells with an abnormal glycosignature and displaying an increased expression of specific glycan-binding receptors. Interestingly, Mgat5 null mice develop clinical signs compatible within autoimmune-like syndrome together with an increased infiltration of specific CD3 + T cells subset identified in SLE patients. Conclusion: These findings point towards the identification of a novel immune player with increased ability to sense abnormal N -glycans, modulating the surrounding immune response. We propose glycosylation as a regulatory mechanism that tips the balance between homeostasis/self-tolerance and autoimmunity opening a potential novel targeted-specific mechanism in SLE pathogenesis. References: [1]Tsokos GC et al. New insights into the immunopathogenesis of systemic lupus erythematosus. Nat Rev Rheumatol. 2016 Nov 22;12(12):716–30. [2]Marinho A et al. Vitamin D supplementation effects on FoxP3 expression in T cells and FoxP3+/IL-17A ratio and clinical course in systemic lupus erythematosus patients: a study in a Portuguese cohort. Immunol Res. 2017 Feb 16;65(1):197–206. [3]Dias AM et al. Metabolic control of T cell immune response through glycans in inflammatory bowel disease. Proc Natl Acad Sci U S A. 2018 May 15;115(20):E4651–60. [4]Pereira MS & Alves I. et al. Glycans as Key Checkpoints of T Cell Activity and Function. Front Immunol. 2018 Nov 27;9:2754. [5]Pinho SS, Reis CA. Glycosylation in cancer: mechanisms and clinical implications. Nat Rev Cancer. 2015 Sep 20;15(9):540–55. [6]Verhelst X et al. Protein Glycosylation as a Diagnostic and Prognostic Marker of Chronic Inflammatory Gastrointestinal and Liver Diseases. Gastroenterology. 2020 Jan 1;158(1):95–110. Acknowledgments: S.S.P. and I.A. acknowledge Group of Studies for Autoimmune diseases (NEDAI) from Portuguese Society of Internal Medicine (SPMI) for Funding and for supporting the attendance at this meeting. Disclosure of Interests: None declared